Trading volume reactions to a change in dividend policy: the Canadian evidence* - RICHARDSON, GORDON; SEFCIK, STEPHAN E.; THOMPSON, REX (Contemporary Accounting Research, 1988)
This study examines the volume of trading in the stock of 34 Canadian companies that initiated a policy of regular cash dividends during the period 1972–1982. Using a time‐series methodology linked to changes in Canadian tax legislation, we test whether the volume of trading surrounding first‐time dividend adoptions declined after 1978, a year when tax legislation changed the taxation of dividends toward tax neutrality for investors in high tax brackets. We observe a significant trading volume decline after 1978, which we interpret as implying that fewer investors wanted to dispose of initial dividend stocks after 1978. The result is inconsistent with dividend irrelevance theories and possibly points to tax clientele relevance in Canada. Résumé. Les auteurs examinent le volume de titres négociés pour 34 sociétés canadiennes ayant mis en place une politique de versement périodique de dividendes en espèces durant la période 1972–1982. À l'aide d'une méthodologie de séries chronologiques liée aux changements apportés à la législation fiscale canadienne, les auteurs vérifient si le volume des titres négociés dans le contexte de l'adoption initiale de cette politique de dividendes a décliné après 1978, année au cours de laquelle le fisc a modifié l'imposition des dividendes pour pencher vers la neutralité fiscale pour les investisseurs appartenant aux tranches d'impôt élevées. Ils observent un déclin appréciable du volume de titres négociés après 1978, déclin qui suppose, selon eux, qu'un moins grand nombre d'investisseurs ont voulu se défaire de telles actions après 1978. Ce résultat s'oppose aux théories de la non‐pertinence du dividende et pourrait indiquer la pertinence de la «clientèle fiscale» au Canada.